Risk factor and outcome for intra-abdominal bleeding in patients with enterocutaneous fistula. Issue 47 (November 2016) - Wu, Lei; Ren, Jianan; Liu, Qinjie; Wang, Gefei; Wu, Xiuwen; Gu, Guosheng; Li, Guanwei; Guo, Kun; Hong, Zhiwu; Hu, Qiongyuan; Ren, Huajian; Li, Jieshou
Abstract : Abstract: Intra-abdominal bleeding is a major and lethal complication in patients with enterocutaneous fistula (ECF) while few studies are involved in this aspect. In the present study, we aimed to investigate the risk factors and assessed the outcome for intra-abdominal bleeding in patients with ECF. A retrospective study was performed from October 2013 to October 2015. Medical records of 67 ECF patients with intra-abdominal bleeding and 134 ECF patients without intra-abdominal bleeding matched as controls were reviewed and analyzed. Logistic regression was performed to evaluate the risk factor of intra-abdominal bleeding in patients with ECF. Outcomes such as mortality, hospital durations, and cost were compared between ECF patients with or without intra-abdominal bleeding. A total of 67 ECF patients suffered intra-abdominal bleeding during hospitalization. In the logistic regression, duodenum fistula (odds ratio [OR]: 3.899, 95% confidence interval [CI]: 1.204–12.634, P  = 0.023), hemorrhage history (OR: 15.846 95% CI: 5.779–43.448, P  < 0.001), and acute kidney injury (OR: 6.350 95% CI: 2.033 – 19.836, P  = 0.001) were independent risk factors for intra-abdominal bleeding in patients with ECF. In addition, the bleeding patients showed a significantly higher mortality rate, prolonged total parenteral nutrition days, hospital and intensive care unit durations, more complications, and increased cost. We revealed the 3 risk factors for intra-abdominal bleeding among ECF patients. Besides, intra-abdominal hemorrhage was associated with a poor prognosis in patients with ECF.